2013
DOI: 10.1016/j.juro.2013.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Pulmonary Embolism Does Not Predict Poor Postoperative Outcomes in Patients with Renal Cell Carcinoma and Venous Thrombus

Abstract: Preoperative pulmonary embolism is not associated with worse early mortality, recurrence or cancer specific survival in patients with renal cell carcinoma and tumor thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…An interesting aspect of this case is the fact that despite considerable amounts of tumor thrombi remaining in the IVC filter, the IVC itself as well as in the iliac veins, there are still no signs of local or any suspicion for metastatic progression after a follow-up of more than 1 year. This suggests -similar to the effect of cytoreductive nephrectomy on systemic metastases or recurrence rates after pulmonary embolism [7,8] -that the cancer cells within the thrombotic metastases might somehow be dependent on the presence of their primary tumor to proliferate and disseminate. The underlying biological mechanisms of this phenomenon remain elusive.…”
Section: Linxweiler Et Almentioning
confidence: 78%
“…An interesting aspect of this case is the fact that despite considerable amounts of tumor thrombi remaining in the IVC filter, the IVC itself as well as in the iliac veins, there are still no signs of local or any suspicion for metastatic progression after a follow-up of more than 1 year. This suggests -similar to the effect of cytoreductive nephrectomy on systemic metastases or recurrence rates after pulmonary embolism [7,8] -that the cancer cells within the thrombotic metastases might somehow be dependent on the presence of their primary tumor to proliferate and disseminate. The underlying biological mechanisms of this phenomenon remain elusive.…”
Section: Linxweiler Et Almentioning
confidence: 78%
“…A recent study in 2013 showed a preoperative pulmonary embolism in 4.4% of renal cell carcinoma patients with proven venous thrombus. 11 Nevertheless, it seems likely that the mechanical obstruction of the vena cava had a significant impact on the development of pulmonary artery embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, abdominal abnormalities, such as RCC, are included in the differential diagnosis of PE in addition to lower limb deep vein thrombosis. Abel et al reported that PE was identified preoperatively in 35 of 782 patients (4.4%) with RCC 10) . However, the incidence of PE due to RCC is relatively rare; identification of RCC as the cause is critical for deciding on the additional surgical therapy along with anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%